Informatics in Control Automation and Robotics Revised and Selected Papers from the International Conference on Informatics in Control Automation and Robotics 2009 - Cetto, Juan Andrade; Filipe, Joaquim; Ferrier, Jean-Louis.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The present book includes a set of selected papers from the fourth (3z(BInternational Conference on Informatics in Control Automation and Robotics(3y (B(ICINCO 2009), held in Milan, Italy, from 2 to 5 July 2009. The conference was organized in three simultaneous tracks: (3z(BIntelligent Control Systems and Optimization(3y(B, (3z(BRobotics and Automation(3y (Band (3z(BSystems Modeling, Signal Processing and Control(3y(B. The book is based on the same structure. ICINCO received 365 paper submissions, not including those of workshops, from 55 countries, in all continents. After a double blind paper review performed by the Program Committee only 34 submissions were accepted as full papers and thus selected for oral presentation, leading to a full paper acceptance ratio of 9%. Additional papers were accepted as short papers and posters. A further refinement was made after the conference, based also on the assessment of presentation quality, so that this book includes the extended and revised versions of the very best papers of ICINCO 2009. Commitment to high quality standards is a major concern of ICINCO that will be maintained in the next editions of this conference, including not only the stringent paper acceptance ratios but also the quality of the program committee, keynote lectures, workshops and logistics.s
Invited Papers -- Part I: Intelligent Control Systems and Optimization -- Part II: Robotics and Automation -- Part III: Signal Processing, Sensors, Systems Modeling and Control.
Keywords: Engineering; Artificial intelligence; Engineering; Control; Robotics and Automation; Artificial Intelligence (incl. Robotics).